Behavior Change Therapy Model for Improving Tooth Brushing Behavior among Children with Mental Retardation - Rohisotul Laily; rasipin rasipin; Supriyana supriyana; Suharyo Hadisaputro; Bedjo Santoso (International Journal of Nursing and Health Services (IJNHS), 2020)
Dental health problems occur in many communities, including mental retardation in children with all of their intellectual limitations, social behavior, and sometimes the weakness in motor coordination. The study aimed to develop and to examine the effectiveness of the behavior change therapy model as an alternative to improving the tooth brushing behavior among children with mental retardation. The Research and Development (R&D) approach was applied in this study. The quasi-Experimental, Pre-test, and Post-test with the non-equivalent control group for examining the effect of the model on health outcome. The research subjects of mental retardation children were divided into the intervention group and the control group. Experts tested by the intervention group validated the model development. Expert validation of the behavior change therapy model gets an average of 86.67 (very decent) as an alternative to improving tooth brushing behavior among children with mental retardation with p-value<0.05. Other results found that the model effectively enhanced the knowledge, gesture, and tooth brushing skills in mental retardation children with p-value <0.05. The therapy model as an alternative strategy was useful and recommended improving tooth brushing behavior among mental retardation children